(untitled) (Fiep Bulletin - online, 2017)
School age represents a special period of growth and development and, therefore, surveillance actions arefundamental. At this stage of life it is important, among other factors, to monitor aspects related to the nutrition of individuals.Through Anthropometry tools it is possible to identify health aspects of children and adolescents in a simple and low cost way. Theobjective of this study was to report and analyze the results of the anthropometric evaluation of schoolchildren. The followingspecific objectives were determined: a) Identify the evolution of growth and body weight of students; B) To compare the evolutionof growth and body weight; C) To study the nutritional aspects of the students. For that, the anthropometric data of 14 8-year-oldmale and female students from a Municipal School of Porto Velho, capital of the state of Rondônia, Brazil, were used. Data onStature, Body Weight and Body Mass Index / BMI were collected in the years 2014, 2015 and 2016. To know the level of normalityof the results, other theoretical references were used in addition to WHO (2007). The result pointed out that the growth aspects ofboth girls and boys are on the rise, although they do not follow numerically what the literature recommends. Regarding bodyweight, this variable developed within normal parameters. Regarding the evolution of BMI, both girls and boys showed aquantitative progression, although these advances, when submitted to statistical analysis, are not significant. Still regarding BMI,both groups were classified below the level of normality.